Preparation and Characterization of Nifedipine-Loaded Dry Medium Internal-Phase Emulsions (Dry MIPEs) to Improve Cellular Permeability - Sukannika Tubtimsri; Yotsanan Weerapol (MDPI AG, 2022)
A nifedipine (NP) dry emulsion was fabricated by the adsorption of medium internal-phase emulsions (MIPEs). Simple homogenizers were first used to mix conventional liquid MIPEs, and then a microfluidizer was used to reduce the resulting emulsions' droplet sizes. The dry MIPEs (solid) were produced by adsorbing the emulsions onto solid carriers with a high surface area. The dry MIPEs were diluted in a simulated gastric fluid under gentle agitation to form emulsions. The diluted dry MIPEs were divided into three groups based on an NP content of 0.3%, 0.5%, and 0.7%, with sizes of 5026-5404 nm, 2583-3233 nm, and 1318-1618 nm in diameter, respectively. Powder X-ray diffraction (PXRD) measurements and differential scanning calorimetry (DSC) were used to characterize the physical properties of the dry MIPEs. The samples contained 0.5% or 0.7% drug, 2-4% surfactant, and 8-16% oil (5RH2/8, 7RH2/8, and 7RH4/16) and showed the characteristic peak for NP. No NP peak was observed in formulations with 0.3% NP and any oil-phase content (3RH2/8, 3RH4/16, and 3RH8/32). The formulations with 0.5% drug, 4-8% surfactant, 16-32% oil (5RH4/16 and 5RH8/32) and those with 0.7% drug, 8% surfactant, and 32% oil (7RH8/32) also did not show the peak for NP. These findings demonstrated that microfluidization improved the solubility of NP in the formulations. The subsequent drug dissolution results were consistent with the DSC thermogram and PXRD pattern results. 3RH2/8, 3RH4/16, 3RH8/32, 5RH4/16, 5RH8/32, and 7RH8/32 were completely dissolved and showed higher dissolved NP amounts than 5RH2/8, 7RH2/8, 7RH4/16, and NP powder. The lowest mean dissolution time was for 7RH8/32 (13.31 ± 0.87 min). Caco-2 cells were used to determine drug uptake, and 7RH8/32 showed the maximum intracellular uptake (10.89%). After storage under accelerated and normal conditions (3 and 6 months), the selected formulations remained stable. The developed formulations can be used to improve NP solubility and absorption.